Pembuatan Studio Mini Sebagai Sarana Branding Product di Era Digital Marketing Pada UMKM Keputih Surabaya - Khoirotunnisa, Fani; Wikartika, Ira; Sibarani, Steven Arrow Rinel; Sari, Rafika (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
Along with the continued development of digital marketing in product marketing today, it is very necessary to be able to improve product branding for Small, Medium, and Micro Enterprises (MSMEs), especially in Keputih Village, Surabaya. The lack of maximum ability in branding the products offered is due to limited facilities in taking good product photos. Product photos can be used as a visual communication medium, because a good product photo can convey the intent of the photo, so as to increase product knowledge. Making a mini studio as a solution to the problem of the availability of facilities to be used as a studio. The implementation of this mini studio creation activity was carried out in mutual cooperation in Keputih Village with simple tools and materials through the KKNT MBKM UPN